2022
DOI: 10.1186/s12864-021-08165-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis of plant ascomycete fungal pathogens with different lifestyles reveals distinctive virulence strategies

Abstract: Background Pathogens have evolved diverse lifestyles and adopted pivotal new roles in both natural ecosystems and human environments. However, the molecular mechanisms underlying their adaptation to new lifestyles are obscure. Comparative genomics was adopted to determine distinct strategies of plant ascomycete fungal pathogens with different lifestyles and to elucidate their distinctive virulence strategies. Results We found that plant ascomycete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Moreover, CBMs that bind to glycoside hydrolases to enhance plant cell wall degradation (e.g., L-rhamnose-binding and starch-binding) and PLs degrading glycosaminoglycans and pectin were also detected among all species analyzed. Our results corroborate previous studies in which the capacity of plant cell wall degradation is linked to fungal lifestyle (necrotrophic, hemibiotrophic, and biotrophic) [ 93 , 94 ]. For instance, some authors have documented that higher numbers of hydrolytic enzymes are most prominent in hemibiotrophs (e.g., M. oryzae , D. longicolla , N. parvum ), necrotrophs (e.g., B. cinerea ), saprobes (e.g., Paraphaeosphaeria sporulosa ), and endophytes/latent pathogens (e.g., Periconia macrospinosa ) than in biotrophs [ 21 , 78 , 93 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, CBMs that bind to glycoside hydrolases to enhance plant cell wall degradation (e.g., L-rhamnose-binding and starch-binding) and PLs degrading glycosaminoglycans and pectin were also detected among all species analyzed. Our results corroborate previous studies in which the capacity of plant cell wall degradation is linked to fungal lifestyle (necrotrophic, hemibiotrophic, and biotrophic) [ 93 , 94 ]. For instance, some authors have documented that higher numbers of hydrolytic enzymes are most prominent in hemibiotrophs (e.g., M. oryzae , D. longicolla , N. parvum ), necrotrophs (e.g., B. cinerea ), saprobes (e.g., Paraphaeosphaeria sporulosa ), and endophytes/latent pathogens (e.g., Periconia macrospinosa ) than in biotrophs [ 21 , 78 , 93 ].…”
Section: Discussionsupporting
confidence: 92%
“…Despite the of loss of genes for key cell wall decomposing enzymes, there is still a functional fine-tuned attack of selective host cell wall polymers by specific enzymes in first host tissue colonization, which is in principle common with other fungal guilds of plant colonizing species, such as endophytes, biotrophic pathogens and hemi-biotrophic species in their growth phase with living plant cells before they enter their necrotrophic phase (Anasontzis et al 2019 ; Bellincampi et al 2014 ). Genome comparisons between different types of ascomycetous plant pathogens revealed that biotrophs have a lower number of genes for plant cell wall degrading than hemi-biotrophs and necrotrophs, as one possible adaptation to living in physiologically active plant tissues (Wang et al 2022 ). Interactions with plant cell walls and plant cell wall degradation abilities of different fungal guilds are certainly the most important topic in the ecology of all kinds of tree-associated fungi.…”
Section: Fungal Communities Associated With Treesmentioning
confidence: 99%
“…Likely also obtained by HGT, the poplar canker pathogen Mycosphaerella populorum expresses a chaetoglobosin-like BGC during growth on poplar wood (Dhillon et al 2015 ). Wang et al ( 2022 ) reported from comparative genomics a correlation with increasing numbers of gene SM clusters from biotrophic to hemi-biotrophic and necrotrophic pathogens. Typical for many ascomycetous plant pathogens, the North-American lethal laurel wilt Raffaelea lauricola and the Eucalyptus leaf blight pathogen Calonectria pseudoreteaudii have greatly increased numbers of distinctive BGCs as compared to the non-pathogenic Raffaelea aguacate and average levels generally found in ascomycetes (Ye et al 2018 ; Zhang et al 2020 ).…”
Section: Fungal Communities Associated With Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes in clusters are not constitutively expressed, and formerly actively expressed genes can become transcriptionally inactive with repeated culturing [ 31 ]. In addition, antiSMASH (a freely available online tool to investigate the presence and diversity of secondary metabolite biosynthesis gene clusters) analyses of fungal genomes showed that ascomycete biotrophs show a lower rate of SM and CAZyme-related gene gain and loss events in the genome [ 32 ]. Taylor et al [ 33 ] predicted SM biosynthetic gene clusters in the genome of Sclerotinia sclerotiorum and analyzed their gene expression during the infection of Brassica napus and reported 80 putative SM clusters.…”
Section: Introductionmentioning
confidence: 99%